Production of essential oil in plants: ontogeny, secretory structures and seasonal variations - Lee, Yee Ling; Ding, Phebe (Universiti Putra Malaysia Press, 2016)
Essential oil production in plants is known to play crucial roles in attractive and defensive mechanism responses to environmental conditions. Various factors are known to determine the chemical variability and yields for specific essential oil bearing plants including genetic, physiology and environment. The purpose of this review is to summarize recent publications on the variation of essential oil and its composition with regards to physiological aspects of the plants.